COVID-19: A Crisis of Borders. Issue 4 (7th October 2021) - Boucher, Anna; Hooijer, Gerda; King, Desmond; Napier, Isabelle; Stears, Marc
ABSTRACT: The public health crisis of COVID-19 has compounded preexisting crises of democratic stability and effective governance, spurring debate about the ability of developed democracies to respond effectively to emergencies confronting their citizens. These crises, much discussed in recent political science, are joined by a further crisis which complicates and reinforces them: A migration crisis. Widespread travel and immigration restrictions instigated the largest and fastest decline in global human mobility in modern history, and COVID-19 may fundamentally change immigration over the longer term. The migration crisis heightens three crucial and preexisting concerns within immigration policy: the role of visa design; the status of undocumented migrants and other migrants without recourse to public funds; and the interaction of immigration and the labor market policy. It could reinforce a rising tide of nationalism and anti-immigrant sentiment, protectionist sentiment within labor-market policy debates, and a K-shaped recovery in migration patterns.